EXAMINING THE IMPACT OF PEOPLE, PROCESS, AND PHYSICAL EVIDENCE ON OUTPATIENT REVISIT INTENTION IN A PRIVATE HOSPITAL RADIOLOGY DEPARTMENT: THE MEDIATING EFFECT OF WORD-OF-MOUTH MARKETING - Sumantri Sumantri; Bayu Wahyudi; Kahar Mulyani (Jurnal Ekonomi Kreatif dan Manajemen Bisnis Digital, 2025)
Patient visits to the Radiology Unit are one of the revenue streams for private hospitals. A decrease in visit volume can raise serious financial concerns, necessitating a clear understanding of the influencing factors so that hospital management can respond with efficient and well-directed strategies. This study aims to analyze how the 3P marketing mix antecendents including people, process, and physical evidence affect revisit intention, with word of mouth acting as a mediating variable, in the context of outpatient services in the Radiology Unit of a private hospital. People, process, and physical evidence are marketing mix factors that are unique to the healthcare service sector. This study is a quantitative study where the data collection method uses a questionnaire filled out by respondents in the study population. There are seven hypothesis lines analyzed using PLS-SEM with data collected from outpatients of the Radiology Unit in a class B private hospital in the city of Depok from November 2024 to February 2025 as many as 182 respondents. The results showed that the physical evidence factor had a positive effect on word of mouth and revisit intention, the process factor had a positive effect on word of mouth but not on revisit intention, and the people factor had no positive effect on either. This study is expected to contribute to the hospital in improving outpatient services in the Radiology Unit.